2018
DOI: 10.1038/s41612-017-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

ENSO relationship to summer rainfall variability and its potential predictability over Arabian Peninsula region

Abstract: The El Niño Southern Oscillation (ENSO) phenomenon is considered to be responsible for rainfall predictability in many regions. Some of its regional teleconnections, such as over the Arabian Peninsula in boreal summer (June-August) season, are not well studied. Therefore, in this paper, the relationship between the summer seasonal mean rainfall and ENSO is analyzed with the aid of a 15-member ensemble of simulations using the Saudi-King Abdulaziz University (KAU) Atmospheric Global Climate Model (AGCM) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…The ENSO atmospheric teleconnections is considered as the leading mode of variability that causes profound effect on global and regional climate and weather events (Azharuddin & Dogar, ; Dogar et al, ; Kumar et al, ; Neelin et al, ; Timmermann et al, ; Trenberth et al, ; Trenberth & Caron, ). It has been shown that the climate of Middle East, in particular the AP region, is strongly impacted by ENSO (Abid et al, ; Athar & Ammar, ; Barlow et al, ; Dogar, Kucharski, et al, ; Dogar, Stenchikov, et al, ; Sandeep & Ajayamohan, ). In this section we emphasized that both the El Niño and La Niña are important modes of variability that should be taken into account while discussing leading climate forcing factors and their climatic impacts in the MENA region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ENSO atmospheric teleconnections is considered as the leading mode of variability that causes profound effect on global and regional climate and weather events (Azharuddin & Dogar, ; Dogar et al, ; Kumar et al, ; Neelin et al, ; Timmermann et al, ; Trenberth et al, ; Trenberth & Caron, ). It has been shown that the climate of Middle East, in particular the AP region, is strongly impacted by ENSO (Abid et al, ; Athar & Ammar, ; Barlow et al, ; Dogar, Kucharski, et al, ; Dogar, Stenchikov, et al, ; Sandeep & Ajayamohan, ). In this section we emphasized that both the El Niño and La Niña are important modes of variability that should be taken into account while discussing leading climate forcing factors and their climatic impacts in the MENA region.…”
Section: Resultsmentioning
confidence: 99%
“…Using comprehensive statistical approaches, Zhang et al () examined in detail the trends in temperature and precipitation indices for Middle East region. Some recent studies have analyzed the response of AP region to ENSO or NAO forcings (see, e.g., Abid et al, ; AlSarmi & Washington, , ; Kumar et al, ; Sandeep & Ajayamohan, ). Nevertheless, the impact of the leading climate factors on the MENA region is marginally explored, and therefore, further studies to improve our understanding are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, linkages between climatic patterns and precipitation have been investigated by a range of statistical methods, such as correlation (Abid et al, 2018), principal component analysis (Luterbacher et al, 2006), empirical orthogonal functions (Hannachi et al, 2007), and regression and canonical analysis (Xoplaki et al, 2004). However, all these methods are limited in capturing the scale-specific feedbacks and interactions between the long-range climatic patterns and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have also indicated that ENSO impacts are very important, especially in the monsoon regions (Ashok et al, , ; Azharuddin & Dogar, ; Dogar et al, ; Dogar et al, ; Shukla, ). By employing global climate model simulations (Almazroui et al, ) and observational/reanalysis products, it has been examined that ENSO teleconnection produces strong impact over the Arabian Peninsula summer rainfall (Abid et al, ). The ENSO strongly impacts the Hadley cell (HC), especially the upward branch of HC that is strongly coupled to the monsoon system.…”
Section: Introductionmentioning
confidence: 99%